Extracción y caracterización fisicoquímica de colágeno a partir de escamas de yaraquí (Semaprochilodus insignis) por hidrólisis mixta con fines nutricionales - Chávez Macedo, Fiorella Margot (2023)
The objective of the research was to obtain type I collagen from the scales of Yaraquí (Semaprochilodus insignis), the study was experimental factorial, as factors temperature and type of acid, on the response percentage of protein. The characterization of the collagen obtained from the optimal treatment was performed by polyacrylamide gel electrophoresis (SDS PAGE), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and amino acid profile by high performance liquid chromatography - HPLC. The treatment with citric acid plus pepsin at 20ºC reported the highest protein percentage of 25,42±1,59%. From the SDS-PAGE analysis, β-chain, α-1and α-2 chain protein bands were evidenced, with molecular weights 245, 100, 75, 63 and 35 kDa. From the structural analysis by FTIR, absorption peaks with amide bonds were reported, Amide A (3298), Amide B (2922), Amine I (1636), Amine II (1541), Amine III (1233). From the SEM, porous fibrils characteristic of collagen were shown. Likewise, the amino acid profile showed characteristic amino acids, glycine at a concentration of 113,97±0,02 mg/g and proline 60,56±0,01 mg/g. Concluding that type I collagen was extracted from yaraquí scales.